A highly efficient white quantum dot light-emitting diode employing magnesium doped zinc oxide as the electron transport layer based on bilayered quantum dot layers. Issue 30 (19th July 2018) - Wang, Lixi; Pan, Jiangyong; Qian, Jianping; Lei, Wei; Wu, Yuanjun; Zhang, Wei; Goto, Daniel Kenneth; Chen, Jing
Abstract : A highly efficient QLED achieving white emission at a low driving voltage is obtained by employing Zn0.95 Mg0.05 O as the electron transport layer. Abstract : Herein, a highly-efficient quantum dot light-emitting diode (QLED) with stacked blue and yellow quantum dot (QD) layers can be demonstrated to output white light. A buffer layer of ZnO nanoparticles (NPs) inserted between two QD layers can prevent them from mixing and penetrating. In order to promote charge balance, Zn0.95 Mg0.05 O was employed as the electron transport layer (ETL), which can block excessive electrons due to the 0.07 eV higher conduction band minimum (CBM) level compared to that of pristine ZnO, leading to the suppression of exciton quenching. In addition, the lower defect concentration and lowered conductivity of Zn0.95 Mg0.05 O due to the reduction of oxygen vacancies by doping the Mg element into ZnO can also benefit the inhibition of exciton quenching. The device can be demonstrated with a maximum luminance current efficiency of 24.6 cd A −1 and power efficiency of 25.8 lm W −1, exhibiting a 19% and 38% enhancement, respectively. The strategy demonstrated here demonstrates a promising way to realize highly efficient white QLEDs and also other optoelectronic devices.